The Effect of Synchronized Forced Running with Chronic Stress on Short, Mid and Long- term Memory in Rats - Radahmadi, Maryam (Tehran University of Medical Sciences, 2012)
PURPOSE: Impairment of learning and memory processes has been demonstrated by many studies using different stressors. Other reports suggested that exercise has a powerful behavioral intervention to improve cognitive function and brain health. In this research, we investigated protective effects of treadmill running on chronic stress–induced memory deficit in rats. METHODS: Fifty male Wistar rats were randomly divided into five groups (n=10) as follows: Control (Co), Sham (Sh), Stress (St), Exercise (Ex) and Stress and Exercise (St & Ex) groups. Chronic restraint stress was applied by 6h/day/21days and also treadmill running at a speed 20-21m/min for 1h/day/21days. Memory function was evaluated by the passive avoidance test in different intervals (1, 7 and 21 days) after foot shock. RESULTS: Our results showed that: 1) Although exercise alone showed beneficial effects especially on short and mid-term memory (P<0.05) in comparison with control group, but synchronized exercise with stress had not significantly improved short, mid and long-term memory deficit in stressed rats. 2) Short and mid-term memory deficit was significantly (P<0.05) observed in synchronized exercise with stress and stress groups with respect to normal rats. 3) Memory deficit in synchronized exercise with stress group was nearly similar to stressed rats. 4) Helpful effects of exercise were less than harmful effects of stress when they were associated together. CONCLUSION: The data correspond to the possibility that although treadmill running alone has helpful effects on learning and memory consolidation, but when it is synchronized with stress there is no significant benefit and protective effects in improvement of memory deficit induced by chronic stress. However, it is has a better effect than no training on memory deficit in stressed rats.